ANALISIS LIKUIDITAS PERBANKAN DALAM MENJAGA STABILITAS SISTEM EKONOMI SESUAI PERATURAN-PERATURAN OTORITAS JASA KEUANGAN (POJK) PADA BANK BPR DI KOTA DENPASAR - Ni Made Ita Indriyani I; Ni Wayan Suartini N; I Nyoman Gede Suparptha W (Nusantara Hasana Berdikari, 2022)
Financial stability is a classic issue that accompanies the economic growth of a country, because it is considered to be positively related to the level of economic growth. The large number of macroeconomic variables that affect these conditions will require monetary policy to be at the forefront of work for supervisors and regulators to support market dynamics. The stronger the economic integration between countries, the greater the currency risk, just as economic fluctuations in one country can cause a domino effect in another. Analysis of banking liquidity in maintaining the stability of the economic system as regulated by the Financial Services Authority (POJK) at rural banks in Denpasar (case study of BPR Lestari Denpasar). This research is classified as quantitative research and is classified as a combined causality study. The sample used in this study was 36. The data analysis method used was classical hypothesis testing, multiple linear regression analysis, deterministic analysis, partial test (t test), and simultaneous test (F test). The results show that bank liquidity and economic stability have the same effect based on the Financial Services Authority (POJK) regulations at Bank BPR Lestari Denpasar City.